Mooki Leepa’s rebellion of February to March 1970: a preliminary examination of motives - Pule, Neville W.; Thabane, Motlatsi (Faculty of the Humanities, University of the Free State, 2010)
This article deals with a well-known but largely under-researched event that occurred in Lesotho during the first three months of 1970, an incident in which members of opposition parties under the leadership of a former Deputy Commissioner of Police, Clement Mooki Leepa, occupied a cave, Lehaha-la-Likhomo, and organised themselves into a force determined to resist police arrest. Using the oral testimony of one key participant, court cases, official reports and secondary sources, the article firstly attempts to situate the incident, and Leepa’s involvement in it, in the context of political divisions that characterised the country’s road to independence and, secondly, to reconstruct the events that took place at the cave. The article mainly argues that, accepting without question the assertion that many of the acts of members of opposition parties in 1970 were attempts to topple government, prevents a deeper understanding of the complex and contradictory political and at times personal reasons and motivations of equally complex individuals and groups who participated in these activities. We have used the terms “rebel” or “rebellion” to describe the incident discussed in this paper, but have done so reluctantly because the men and their backers’ plans were nipped in the bud, and never came to anything.
Keywords: Lesotho; Lehaha-la-Likhomo; Police